Developing Module of Personal-Social Guidance for Guidance and Counseling Teachers in Special Region of Yogyakarta to Increase Psychological Preparedness of Senior High School Students in Facing Natural Disaster - Yulia Ayriza (Jurnal Kependidikan, 2009)
This research aim to: (1) assess the need of Guidance and Counseling teachers concerning module material for increasing psychological preparedness of senior high school students in facing natural disaster; (2) develop and also validate module mentioned at the first purpose of this research. This research apply research and development approach for module validation and development. The research variable in this study is psychological preparedness in facing natural disaster; Psychological preparedness consisted of cognitive, affective and psychomotoric readiness; while natural disaster anticipated in this module cover earthquake, mount erupt and tropical cyclone. Research subject consist of 48 Guidance and Counseling teachers in special region of Yogyakarta for the purpose of need assessment; and for testing module validity, besides tested by three expert people, they are each expert in Guidance and Counseling, expert in natural disaster and mitigation, and expert in media, module is also tried out to user subject, that is Guidance and Counseling teachers of senior high school in special region of Yogyakarta. The try out sequentially involve 6 people at initial field, 15 people at main field, and 65 people at operational field. Instruments applied to collect data are either opened or closed questionnaires. The collected data, the quantitative as well as the qualitative one were analyzed descriptively. Results obtained from this research are: (1) Material required by Guidance and Counseling teachers for module of psychological preparedness in facing natural disaster cover cognitive aspect ( 14,58%), affective aspect ( 31,25%) and psychomotoric aspect ( 52,08%). (2) The module of "Personal-Social Guidance for increasing Psychological Preparedness of Students in Facing Natural Disaster" which is developed besides based on result of need assessment, also based on literature study by considering potential disaster for special region of Yogyakarta, therefore module developed cover three activities of personal-social services, each to face natural disaster of (a) earthquake, (b) mount erupt, and (c) tropical cyclone.(3) module validated is valued proper either in appearance or in concept, and also useful as media for assisting to perform service of personal-social guidance to increase psychological preparedness of senior high school students in facing natural disaster. Further, the module is valued self-contained for having fulfilled acceptance criterion ( subject reach 80 % minimum understanding) at the test of content understanding and module readability. Keywords: Module of Personal-Social Guidance, Psychological Preparedness in Facing Natural Disaster